Utilization of complementary therapy in midwife services in the City of Surabaya - Nova Elok Mardliyana; Irma Maya Puspita; Annisa’ Wigati Wigati Rozifa (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background : Midwifery services are provided by midwives with conditions and licenses by applicable regulations and laws to practice midwifery. Midwife can combine conventional and complementary therapies in providing health services.Objectives: Complementary therapy in midwifery services is a choice for pregnant women, maternity, postpartum, infants, and toddlers to improve health status with promotive, preventive, curative, rehabilitative efforts with high quality, safety, and effectiveness. In addition, complementary therapies can reduce medical intervention.Methods: The research method used is a mixture of quantitative and qualitative methods. Data collection was carried out by survey without intervention on research subjects. The survey was carried out in two stages, first by distributing questionnaires to collect quantitative data, then continued with the second stage, namely in-depth interviews with subjects who met the criteria from quantitative data obtained by the researcher.Results: This study shows that the independent practice of midwives in Surabaya is as much as 54% (44 people) have applied. In comparison, 46% (37 people) have not implemented complementary therapies in their midwifery services. Types of complementary therapies applied were baby massage and SPA 30% (23 people), oxytocin massage 19% (15 people), hypnotherapy (hypnobirthing) 14% (11 people), yoga (prenatal and postnatal) 12% (9 people), massage for pregnant women 10% (7 people), Acupressure 5% (4 people), Aromatherapy 5% (4 people), Herbal Medicines or Traditional Herbs 5% (4 people).Conclusions: Complementary midwifery services are an option to reduce medical interventions during pregnancy, childbirth, the puerperium, infants, and toddlers.